CSR과 반생산적 업무행동 간의 관계에서 도덕적 정체성의 조절효과: 도덕-행동 일치성과 도덕적 허가 현상 - 방도(Fang, Tao); 성상현(Sung, Sanghyeon) (대한경영학회지, 2021)
이 논문에서는 구성원이 인식한 CSR이 반생산적 업무행동과 갖는 관계에서 도덕적 정체성이 미치는 영향에대해 탐색하였다. 도덕적 정체성을 내면화된 도덕적 정체성과 상징화된 도덕적 정체성으로 구분하여 도덕-행동의 일치 효과와 도덕적 허가 현상에 대해 논의하고, 이를 바탕으로 CSR이 가진 긍정적 효과와 도덕적 허가현상의 존재 여부를 분석하였다. 연구 결과, 구성원이 인식한 CSR은 반생산적 업무행동을 감소시키는 직접적 영향을 보였으며, 내면화된도덕적 정체성과 결합될 때 반생산적 업무행동을 보다 많이 감소시켰다. 구성원이 인식한 사회적 CSR은 대인지향 및 조직지향 반생산적 업무행동을 모두 감소시키는 효과를 나타냈다. 나아가 개인의 내면화된 도덕적정체성이 높으면 조직구성원이 인식한 사회적 CSR과 대인지향 및 조직지향 반생산적 업무행동 간에 모두부(-)적 관계가 강화되었다. 즉, 내면화된 도덕적 정체성이 높은 구성원이 CSR 인식이 높으면 조직에 긍정적인효과가 더 증가된다는 것이다. 반면, 개인의 상징화된 도덕적 정체성이 높으면 조직구성원이 인식한 사회적CSR과 조직지향 반생산적 업무행동 사이의 부(-)적 관계가 약화되었다. 이것은 개인의 상징화된 도덕적 정체성이 강하면 CSR이 갖는 긍정적 효과가 감소되며 CSR이 도덕적 허가를 유발하여 오히려 반생산적 행동의감소를 약화시킬 수 있음을 시사한다. 나아가 상징화된 도덕적 정체성이 낮은 경우에는 CSR 인식이 조직관련반생산적 업무행동을 줄이는데 보다 큰 영향력을 갖는 것으로 나타났다. 본 연구를 통해 CSR에 대한 구성원의 인식이 경영상 중요한 과제이며 기업의 CSR 전략에서 경영상 당연시되는 사업관련 활동을 넘어서 사회적 책임을 수행하는 활동을 중시하는 것이 바람직하다는 점을 확인하였다. 인적자원의 모집 및 선발과 인력개발 등 인적자원관리에서 조직구성원의 내면화된 도덕적 정체성을 높이고상징화된 도덕적 정체성은 낮추는 것이 조직의 생산성에 바람직하며 CSR이 유발할 수 있는 도덕적 허가현상을 줄일 수 있을 것이다. In this paper the influences of the moral identity on the relationship between the perceived CSR and counterproductive work behavior are discussed. To elaborate the phenomena of the moral licensing and the moral consistency effects through empirical analysis, we divided the moral identity into two types, which are the internalized moral identity and the symbolized moral identity. We investigated whether the positive influence of CSR as well as the moral licensing effect from CSR exists by empirical analysis based on the sample collected by workers in China. For this investigation hypotheses were developed based on the related theories and reasoning. The interaction effects between the perceived CSR and two types of moral identity as well as the main effect were tested by the following hypotheses: H1: The perceived CSR by employees would have negative relationship with the counterproductive work behavior. H2: If the internalized moral identity become higher, counterproductive work behavior would be more reduced by the perceived CSR of employees. H3: If the symbolized moral identity become higher, counterproductive work behavior would be more worsened even the perceived CSR of employees is high. The following figure shows the research model: The analysis proved that the perceived CSR significantly reduces the counterproductive work behavior including both of the interpersonal and the organization-oriented ones. Furthermore, the internalized moral identity strengthened the relationship between the perceived pro-social CSR and the reduction of overall counterproductive work behavior. On the other hand, the symbolized moral identity weakened the relationship between the perceived pro-social CSR and the reduction of organization-oriented counterproductive work behavior, and its impact was stronger more than the impact on the interpersonal counterproductive work behavior. The results imply that the moral identity symbolization impedes the positive effect of CSR to organizational performance because it provokes the moral licensing effect which can be resulted into the counterproductive work behavior. In addition to CSR itself, the perception of employees about the firm CSR program is important for effective management. We found some statistical evidences that the CSR activities for business purpose could be less effective compared to the pro-social CSR by this research. CSR, of course, intends to provide social values to wide range of stakeholders even there are no direct business relations, but if the CSR is focused to business purposes it cannot contribute even to its business performance. Thus it would be desirable to put more importance to pro-social CSR considering that CSR has its roots to the creation of social values. The development of human resources who have high internalized moral identity and less symbolized moral identity is necessary not only to prevent the moral licensing and its negative impact, but also to enhance moral consistency that can be resulted into productive work behavior. KCI Citation Count: 1